Time Management Behavior: Qualitative Exploration Among College Students - Lubis, Dewi Rindiani; Sevrika, Hevriani; Asty, Herfyna (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Time management behavior includes a series of actions and habits that individuals do to use their time effectively. This study aims to identify how students apply time management behavior to maximize their personal learning for English language students. This study uses a qualitative methodology. This study uses a purposive sampling technique. This study uses an instrument in the form of interviews by asking questions to participants in the form of a questionnaire. The respondents in this study were 6 students majoring in English education class of 2022 at the University of PGRI West Sumatra. From direct interviews conducted by researchers, the results obtained that students use time management behavior to maximize their personal learning in order to obtain good academic results. So the researcher concluded that the application of time management behavior plays a very important role in the process of students' personal learning. The data shows that students who apply effective time management strategies tend to have better academic achievement than those who do not apply them. Good time management behavior helps students plan and organize their learning activities more systematically.